Cell cycle-related kinase mediates viral-host signalling to promote hepatitis B virus-associated hepatocarcinogenesis. Issue 11 (17th January 2014) - Yu, Zhuo; Gao, Yue-Qiu; Feng, Hai; Lee, Ying-Ying; Li, May S; Tian, Yuan; Go, Minnie Y Y; Yu, Dae-Yeul; Cheung, Yue-Sun; Lai, Paul B S; Yu, Jun; Wong, Vincent W S; et al.
Abstract : Background: Androgen receptor (AR) signalling contributes to male predominance in hepatocellular carcinoma (HCC), which is more pronounced in HBV-endemic areas. Cell cycle-related kinase (CCRK) is essential for AR-induced hepatocarcinogenesis but its molecular function in HBV-associated HCC remains obscure. Objective: To determine the molecular function of CCRK in HBV-associated HCC. Design: Transcriptional regulation was assessed by chromatin immunoprecipitation, promoter mutation and luciferase reporter assays. Hepatocellular proliferation and tumourigenesis were examined by colony formation, soft agar assays and using HBV X protein (HBx) transgenic mice with low-dose exposure to diethylnitrosamine. Protein expressions were examined in clinical samples and correlated with patient survival by log-rank Mantel–Cox test. Results: Overexpression of CCRK, but not its kinase-defective mutant, activated β-catenin/T cell factor signalling through phosphorylation of glycogen synthase kinase-3β (GSK-3β) at Ser9, led to upregulation of AR transcriptional activity and, subsequently, expression of HBx. The viral transactivator in turn induced CCRK expression through enhanced AR signalling, thus forming a positive regulatory loop. RNA interference silencing of CCRK, which suppressed the CCRK/GSK-3β/β-catenin/AR regulatory loop, significantly suppressed HBx-induced hepatocellular proliferation (p=0.001) and transformation (p<0.001) and remarkably reduced >80% diethylnitrosamine-mediated hepatocarcinogenesis in HBx transgenic mice. Finally, patients with HBV-associated HCC with concordant overexpression of CCRK, GSK-3β phosphorylation at Ser9, active dephosphorylated β-catenin and AR phosphorylation at Ser81 had poorer overall (HR=31.26, p<0.0001) and disease-free (HR=3.60, p<0.01) survival rates. Conclusions: Our findings highlight the critical role of CCRK in a self-reinforcing circuitry that regulates HBV-associated hepatocarcinogenesis. Further characterisation of this intricate viral-host signalling may provide new prognostic biomarkers and therapeutic targets for HCC treatment.